Explication of the mixture of Piper betle and Eugenia polyantha on oral bacteria - Neneng Nurjanah; Megananda Hiranya Putri; Yenni Hendriani Praptiwi; Dewi Sodja Laela; Susi Sukmasari (Healthcare in Low-resource Settings)
The aim of this study was to analyze the effectiveness of the mixtures of Eugenia polyantha (EP) and Piper betle (PB) leaves against oral bacteria. Four compositions of EP and PB were made and observed on tryptic soy agar (TSA), blood agar (BA), MacConkey agar (MCA), and mannitol salt agar (MSA). Inhibition analysis was conducted at concentrations of 20%, 30%, 40%, 50%, and 60%. Our study results indicate that Staphylococcus aureus exhibited growth on BA, bacterial colonies were identified on MSA, and serological tests confirmed coagulation. A biochemical test conducted on an MCA sample revealed several species within the Enterobacteriaceae family, including Escherichia coli, Pseudomonas, Klebsiella, and Proteus. The highest level of inhibition was observed with the sixth toothbrush (K4). Significant differences in inhibition were noted among the various groups (K1, K2, K3, K4, and controls), with the diameter of inhibition for each combination yielding p<0.05. However, the differences in inhibition between the combinations themselves were not statistically significant, with p>0.05. Streptococcus sp, Klebsiella sp, Enterobacteriaceae sp (Coliform sp), Pseudomonas, and Staphylococcus aureus are the contaminant bacteria on used toothbrushes. The highest inhibition level and bactericidal properties were achieved by mixing 70% bay leaf (Eugenia polyantha) and 30% betel leaf infusion.